2004
DOI: 10.1002/marc.200400235
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Scanning Force Microscopy of Macromolecular Conformational Transitions

Abstract: Summary: Comb‐like macromolecules were adsorbed on mica and imaged by scanning force microscopy in real time as they underwent a transition from an extended worm‐like conformation to globuli and vice versa. The conformational transition was effected by coadsorption of ethanol and water molecules. Coadsorption of the small molecules allowed manipulation of the adherence and spreading of the macromolecules, thus effecting the reptation like stretching and collapse of the single molecules.SFM images of three indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 32 publications
3
47
0
1
Order By: Relevance
“…Besides, it was possible to perform many successive cycles of conformational manipulation with the same macromolecules when after first cycle of compaction/extension one might induce second, third and so on, by means of cyclic changing of the vapour environment. [212,215] Even after a dozen of successive cycles performed during several days in total, at every single step the general course of the transformations was observed to be absolutely the same. [215] This observation somehow disagrees with the report of Glynos et al [273] They found out that a macromolecular island of an amphiphilic polymer was spontaneously compacting on mica at ambient conditions during two days of SFM observation.…”
Section: Vapour-induced Conformational Transitions Of Comb-like Macromentioning
confidence: 92%
See 2 more Smart Citations
“…Besides, it was possible to perform many successive cycles of conformational manipulation with the same macromolecules when after first cycle of compaction/extension one might induce second, third and so on, by means of cyclic changing of the vapour environment. [212,215] Even after a dozen of successive cycles performed during several days in total, at every single step the general course of the transformations was observed to be absolutely the same. [215] This observation somehow disagrees with the report of Glynos et al [273] They found out that a macromolecular island of an amphiphilic polymer was spontaneously compacting on mica at ambient conditions during two days of SFM observation.…”
Section: Vapour-induced Conformational Transitions Of Comb-like Macromentioning
confidence: 92%
“…Indeed, they used to be observed also for definitely isolated single macromolecules, as can be noticed in Figure 5 and 6, see also ref. [212] for further details. Besides, it was possible to perform many successive cycles of conformational manipulation with the same macromolecules when after first cycle of compaction/extension one might induce second, third and so on, by means of cyclic changing of the vapour environment.…”
Section: Vapour-induced Conformational Transitions Of Comb-like Macromentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility to induce collapsereadsorption comprises an exposure of the molecule to different vapors. [9,10] Relying on periodical variation of the number of adsorbed monomer units of one of the blocks and, therefore, of the friction force, one can expect fulfillment of the second condition. Finally, the third condition is provided by the structure of the surface which is patterned by the stripes, Figure 1.…”
Section: Communicationmentioning
confidence: 99%
“…Various types of stimuli, e.g., temperature, pH, ionic strength, solvent vapors, light, or an electrical field, can affect properties and conformation of polymers [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%